1982
DOI: 10.1177/003693308202700206
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Endometriosis with Reduced Dosage Schedules of Danazol

Abstract: Experience of the treatment of endometriosis with danazol compares very favourably with the previous use of an oestrogen-progestogen combination in this condition. Symptoms were relieved more rapidly and for longer periods of time. The response to various dose regimes of danazol reveals that 200 mg daily may be adequate for most cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
1987
1987

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…However, there were only five patients in each treatment group. On the other hand, Chalmers (1982) reported that 37 out of 40 women treated with 200 mg/day were promptly relieved of symptoms and this encouraged him to state that 200 mg/day was adequate in most patients. In a series of 38 patients, Moore et al…”
Section: Discussionmentioning
confidence: 99%
“…However, there were only five patients in each treatment group. On the other hand, Chalmers (1982) reported that 37 out of 40 women treated with 200 mg/day were promptly relieved of symptoms and this encouraged him to state that 200 mg/day was adequate in most patients. In a series of 38 patients, Moore et al…”
Section: Discussionmentioning
confidence: 99%